EFEK MODERASI KUALITAS PELAYANAN ATAS PENGARUH PENGETAHUAN PAJAK, KESADARAN WAJIB PAJAK, DAN SANKSI PAJAK PADA KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Vania Rahma Azura; Esti Damayanti (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This study uses a quantitative method using primary data collected by distributing questionnaires to motor vehicle taxpayers registered in Bekasi City. The number of respondents in this research amounted to 100 taxpayers. Based on the results of the analysis of this study it can be seen that, variable tax knowledge and taxpayer awareness shows the same result, namely that there is no significant effect on Motor Vehicle Taxpayer Compliance. However, in tax sanctions, it shows different results, namely it has a significant effect on Motor Vehicle Taxpayer Compliance. Based on the results of research using service quality as a moderating variable, it can be seen that, the interaction of tax knowledge and taxpayer awareness with service quality has no significant effect on motor vehicle taxpayer compliance, but the interaction of tax sanctions with quality services have a significant effect on motor vehicle tax compliance. It is hoped that this research will provide benefits to the relevant agencies by providing corrections to the services of tax collecting institutions so that comfort can be created in order to increase taxpayer compliance in paying motor vehicle taxes